Evaluating the experience of the Olympic and Paralympic Games in the career histories of elite equestrian athletes. - de Haan, D. (University Loughborough, 2015)
Equestrian sport has been present on the Modern Olympic programme since 1900 with Para-Equestrian Dressage making its debut at the 1996 Paralympic Games. Due to the combined governance of Olympic and Paralympic versions of the sport, the mixed gender of competition and the potential age range of competitors, equestrian sport provides an opportunity through which to understand a unique context of athlete experience. This thesis has sought to identify and evaluate athlete experience within the context of the Olympic and Paralympic Games and to place this experience within the wider career histories of members of the British Equestrian Team. This study utilised a combination of a systematic literature review methodology and ethnographic data collection and analysis with a critical realist approach, creating a framework that values interpretive insights into how the subjects perceive and construct their world whilst at the same time considering ways in which the literature and individual subjects identify, comment on, and frame the reality of the world of equestrian sport. This study has resulted in the emergence of six themes pertaining to experiencing the games; equestrian sporting culture, identity, values, challenges, performance support and success. Results show many similarities and shared experiences for both the Olympic and Paralympic equestrian athletes. The differences regarding the lived experience for these athletes are predominantly associated with the development of the sport, the relative short Paralympic history of equestrian sport in comparison to the Olympic disciplines, and the place of the Games in the context of the riders career histories. Recognising and understanding the kinds of satisfactions and challenges that individuals experience, the significant features of their athlete identity, and the structural constraints and opportunities of their environment may help identify and design the services and provision required to support the athletes through this elite sporting experience.